Genotypic and phenotypic variability in mango (Mangifera indica L.) (Bangladesh Journal of Agricultural Research, 2013)
Sixty mango genotypes were studied to find out their variability, heritability, and genetic advance. Significant variations were observed in 20 characters. There were also considerable differences between the genotypic and the phenotypic coefficients of variation for almost all the characters which indicated the influence of environment on the expression of these traits. Among the studied characters, GCV and PCV were high for weight of harvested fruits per plant, % fruit harvest per inflorescence, % initial fruit set per inflorescence, number of fruits per plant and number of main branches per inflorescence. All the characters showed considerably high heritability which ranged from 56.21 to 98.24% and the genetic advance (as % of mean) was high for the maximum traits. High heritability coupled with high genetic advance was observed in weight of harvested fruits per plant, % initial fruit set per inflorescence, % of flowering shoot, number of inflorescences per shoot, percent fruit harvest per inflorescence, number of main branches per inflorescence, number of fruits per plant, number of inflorescences per shoot, plant height (cm), and percent perfect flowers which indicated that these characters were less influenced by environment confirming predominance of additive gene action and therefore, selection in favour of these characters would be feasible for yield improvement of mango. DOI: http://dx.doi.org/10.3329/bjar.v37i4.14393 Bangladesh J. Agril. Res. 37(4): 683-690, December 2012